Augmentation of pulmonary blood flow and cardiac output by non-invasive external ventilation late after Fontan palliation. Issue 2 (6th July 2020) - Charla, Pradeepkumar; Karur, Gauri Rani; Yamamura, Kenichiro; Yoo, Shi-Joon; Granton, John T; Oechslin, Erwin N; Shah, Ashish; Benson, Leland N; Honjo, Osami; Mertens, Luc; Alonso-Gonzalez, Rafael; Hanneman, Kate; et al.
Abstract : Objectives: Although a life-preserving surgery for children with single ventricle physiology, the Fontan palliation is associated with striking morbidity and mortality with advancing age. Our primary objective was to evaluate the impact of non-invasive, external, thoraco-abdominal ventilation on pulmonary blood flow (PBF) and cardiac output (CO) as measured by cardiovascular magnetic resonance (CMR) imaging in adult Fontan subjects. Methods: Adults with a dominant left ventricle post-Fontan palliation (lateral tunnel or extracardiac connections) and healthy controls matched by sex and age were studied. We evaluated vascular flows using phase-contrast CMR imaging during unassisted breathing, negative pressure ventilation (NPV) and biphasic ventilation (BPV). Measurements were made within target vessels (aorta, pulmonary arteries, vena cavae and Fontan circuit) at baseline and during each ventilation mode. Results: Ten Fontan subjects (50% male, 24.5 years (IQR 20.8–34.0)) and 10 matched controls were studied. Changes in PBF and CO, respectively, were greater following BPV as compared with NPV. In subjects during NPV, PBF increased by 8% (Δ0.20 L/min/m 2 (0.10–0.53), p=0.011) while CO did not change significantly (Δ0.17 L/min/m 2 (−0.11–0.23), p=0.432); during BPV, PBF increased by 25% (Δ0.61 L/min/m 2 (0.20–0.84), p=0.002) and CO increased by 16% (Δ0.47 L/min/m 2 (0.21–0.71), p=0.010). Following BPV, change in PBF and CO were both significantly higher in subjects versus controls (0.61 L/min/m 2 (0.2–0.84) vs −0.27 L/min/m 2 (−0.55–0.13), p=0.001; and 0.47 L/min/m 2 (0.21–0.71) vs 0.07 L/min/m 2 (−0.47–0.33), p=0.034, respectively). Conclusion: External ventilation acutely augments PBF and CO in adult Fontan subjects. Confirmation of these findings in larger populations with longer duration of ventilation and extended follow-up will be required to determine sustainability of haemodynamic effects.